2019
DOI: 10.21475/ajcs.19.13.01.p1431
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of grain yield and 2-acetyl-1-pyrroline (2AP) content in leaves and grain of two Thai fragrant rice cultivars cultivated at greenhouse and open-air conditions

Abstract: To verify how different growing environments affect the aroma quality and production yield of fragrant rice, two commercial Thai fragrant rice cultivars, Khao Dawk Mali 105 (KDML 105) and Pathum Thani 1 (PTT 1) were grown in a greenhouse and also open air. Between the two growing environments, the temperature difference averaged 6 ºC. Each rice cultivar was grown in clay loam and sandy loam soils. In addition, a water stress treatment was applied at the beginning of the grain filling stage and onward. Determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The high 2AP level in the KDML105 rice leaves led to a high 2AP level in the rice grains grown in clay and sandy soil [56]. Therefore, in the present study, it was expected that the enhancement of the 2AP level in the leaves of KDML105 rice seedlings by ST-PGPR inoculation might lead to high 2AP in the rice grains.…”
Section: Discussionmentioning
confidence: 61%
“…The high 2AP level in the KDML105 rice leaves led to a high 2AP level in the rice grains grown in clay and sandy soil [56]. Therefore, in the present study, it was expected that the enhancement of the 2AP level in the leaves of KDML105 rice seedlings by ST-PGPR inoculation might lead to high 2AP in the rice grains.…”
Section: Discussionmentioning
confidence: 61%
“…Quantification of 2AP in samples was performed according to the method of Boontakham et al (2019). A static headspace auto-sampler (Model G1888, Agilent Technologies, CA, USA) coupled to an Agilent 6890 Series GC system equipped with an NPD detector was used.…”
Section: Quantification Of 2-acetyl-1-pyrroline In Leaves and Seeds O...mentioning
confidence: 99%
“…Singh, & Khush, 2000). Water stress treatment of KDML 105 after heading increases the amount of 2AP by 18% in leaves and 22% in grains (Boontakham et al, 2019). Another report described the correlation between 22 different locations possessing eight different soil textures in the northeastern part of Thailand and the 2AP content of KDML 105 rice grains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice aroma was regarded as one of the most critical quality characters (Das et al 2018), aroma intensities are closely related to the mixture of aroma compounds in rice (Sansenya et al 2018). The 2-acetyl-1-pyrroline (2AP) was reported as a crucial volatile compound involved in the intricate volatile chemistry of aroma in fragrant rice (Ren et al 2017;Boontakham et al 2019), which can be determined in all parts of fragrant rice excluding root (Maraval et al 2010;Mo et al 2015). In recent times, some studies focusing on the formation of aroma have revealed that the betaine-aldehyde dehydrogenase (BADH)-related gene is responsible for the biosynthesis and up-down regulation of 2AP (Bradbury et al 2005;Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%